2023
DOI: 10.1002/glia.24431
|View full text |Cite
|
Sign up to set email alerts
|

Glial modulation of the parallel memory formation

Abstract: Actions from glial cells could affect the readiness and efficacy of learning and memory. Using a mouse cerebellar-dependent horizontal optokinetic response motor learning paradigm, short-term memory (STM) formation during the online training period and long-term memory (LTM) formation during the offline rest period were studied. A large variability of online and offline learning efficacies was found. The early bloomers with booming STM often had a suppressed LTM formation and late bloomers with no apparent acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…We have shown above that the frequency-locked vasomotion in the cortex also got entrained with repeated training sessions ( Figure 3 ). It has been shown that HOKR performance increase relies on the neuronal and glial activity in the cerebellar flocculus ( Kanaya et al, 2023 ). We next evaluated whether the plasticity of the vasomotion dynamics in the flocculus correlates with the HOKR performance increase.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have shown above that the frequency-locked vasomotion in the cortex also got entrained with repeated training sessions ( Figure 3 ). It has been shown that HOKR performance increase relies on the neuronal and glial activity in the cerebellar flocculus ( Kanaya et al, 2023 ). We next evaluated whether the plasticity of the vasomotion dynamics in the flocculus correlates with the HOKR performance increase.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that vasomotion enhancement may increase the meta-plasticity and provide a basis for efficient neuronal plasticity to occur. In the cerebellum, neuron-to-astrocyte (or Bergmann glia) ( Matsui et al, 2005 ; Matsui and Jahr, 2004 ; Matsui and Jahr, 2003 ) and astrocyte-to-neuron ( Beppu et al, 2021 ; Beppu et al, 2014 ; Sasaki et al, 2012 ) signaling pathways have been identified and such neuron-astrocyte interaction has been shown to be essential for the online HOKR learning to occur ( Kanaya et al, 2023 ). Late offline HOKR learning was dependent in part on the phagocytosis activity of astrocytes ( Morizawa et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that vasomotion enhancement may increase the meta-plasticity and provide a basis for efficient neuronal plasticity to occur. In the cerebellum, neuron-to-astrocyte (or Bergmann glia) (Matsui et al, 2005; Matsui and Jahr, 2004, 2003) and astrocyte-to-neuron (Beppu et al, 2021, 2014; Sasaki et al, 2012) signaling pathways have been identified and such neuron-astrocyte interaction has been shown to be essential for the online HOKR learning to occur (Kanaya et al, 2023). Late offline HOKR learning was dependent in part on the phagocytosis activity of astrocytes (Morizawa et al, 2022).…”
Section: Discussionmentioning
confidence: 99%

Plastic vasomotion entrainment

Sasaki,
Imai,
Ikoma
et al. 2023
Preprint
Self Cite